Pengaruh Kompetensi Digital dan Motivasi Kerja Terhadap Kinerja Pegawai Negeri Sipil di Inspektorat Kota Metro - Amalia Ratna Sari; M. Oktaviannur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The implementation of the Electronic-Based Government System (SPBE) requires civil servants, particularly Internal Government Supervisory Apparatus (APIP), to possess adequate digital competence and strong work motivation in order to support effective and accountable supervisory performance. The Metro City Inspectorate, as a regional APIP institution, still faces challenges related to digital adaptation and work motivation that affect employee performance. This study aims to analyze the effect of digital competence and work motivation on employee performance at the Metro City Inspectorate, both partially and simultaneously. A quantitative research approach was employed using a survey method involving all 52 employees of the Metro City Inspectorate. Data were collected using questionnaires and analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. The results show that digital competence has a positive and significant effect on employee performance, with a path coefficient of 0.418, a t-statistic value of 4.389, and a p-value of 0.000. Work motivation also has a positive and significant effect on employee performance, with a path coefficient of 0.512, a t-statistic value of 5.275, and a p-value of 0.000, and is identified as the most dominant variable. Simultaneously, digital competence and work motivation are able to explain 78.0% of the variation in employee performance, with an R-square value of 0.780, This result indicates that digital competence and work motivation play a very important role in determining employee performance. This study concludes that improving employee performance at the Metro City Inspectorate requires strengthening digital competence and work motivation simultaneously.